Role of silent mutations in KRAS-mutant tumors - Jun Lu; Chao Zhou; Feng Pan; Hongyu Liu; Haohua Jiang; Hua Zhong; Baohui Han; Xiangxiang Pan (Chinese Medical Journal)
Abstract. Silent mutations within the RAS gene have garnered increasing attention for their potential roles in tumorigenesis and therapeutic strategies. Kirsten-RAS (KRAS) mutations, predominantly oncogenic, are pivotal drivers in various cancers. While extensive research has elucidated the molecular mechanisms and biological consequences of active KRAS mutations, the functional significance of silent mutations remains relatively understudied. This review synthesizes current knowledge on KRAS silent mutations, highlighting their impact on cancer development. Silent mutations, which do not alter protein sequences but can affect RNA stability and translational efficiency, pose intriguing questions regarding their contribution to tumor biology. Understanding these mutations is crucial for comprehensively unraveling KRAS-driven oncogenesis and exploring novel therapeutic avenues. Moreover, investigations into the clinical implications of silent mutations in KRAS-mutant tumors suggest potential diagnostic and therapeutic strategies. Despite being in early stages, research on KRAS silent mutations holds promise for uncovering novel insights that could inform personalized cancer treatments. In conclusion, this review underscores the evolving landscape of KRAS silent mutations, advocating for further exploration to bridge fundamental biology with clinical applications in oncology.